MODEL OF STUDENTS’ DISCIPLINE ATTITUDE FORMATION IN SD NEGERI 2 HARAPAN JAYA - Resty Diana Putri; Riswandi Riswandi; Maman Surahman; Erni Mustakim (JPSD (Jurnal Pendidikan Sekolah Dasar), 2018)
This research aims to describe and explain the model of student’s discipline attitude formation. The method used was descriptive with qualitative approach. The data were collected through observation, interview and documentation. The data were analyzed by using Miles and Huberman’s model. The data source consisted of principal, teachers and students. The results: (1) effort to form student’s discipline attitude, (a) planning, (b) school program, (c) activity, (d) implementation of activity. (2) school commitment in forming student’s discipline attitude, (a) affective, (b) continuance, (c) normative. (3) supporting factors: parents, principals and teachers, the willngness of the students. (4) the school's assessment using social attitude journals. Through these results, the model for the establishment of students’s discipline attitude formation included the pre-implementation stage, containing the planning; implementation, containing the implementation of activities, carrying capacity, attitudes would be assessed to determine follow-up. The whole stage was accompanied by commitment from principals, teachers, parents, and students.Keywords: attitude formation, discipline, commitment, attitude assessment.